Development of large shallow Lake Peipsi (North-Eastern Europe) over the Holocene based on the stratigraphy of phosphorus fractions - Kisand, Anu; Kirsi, Anna-Liisa; Ehapalu, Kristiina; Alliksaar, Tiiu; Heinsalu, Atko; Tõnno, Ilmar; Leeben, Aina; Nõges, Peeter (Journal of paleolimnology, 2017)
We studied high-resolution stratigraphy of phosphorus (P) forms in the Holocene sediments of large shallow Lake Peipsi (Estonia/Russia) in order to evaluate the lake ecosystem response to environmental changes and track the lake’s eutrophication history. We distinguished four main periods in the history of Lake Peipsi, each having likely different factors responsible for the distribution pattern of P fractions in the sediment record. We suggest that in the oldest period, from ca. 10.4 up to 7.3 cal ka BP, the sediment composition was mainly determined by rising water level, the second period dated 7.3–2.3 cal ka BP was governed mainly by stable hydrology and P loading, while the third period between 2.3 and 0 cal ka BP was primarily influenced by emerging anthropogenic impact. The sediments from the last period since 1950 are subject of ongoing diagenetic processes but still reflect rapid eutrophication of the lake. Comparison of the results with periods derived from other sediment proxies proved the usability of P fractions stratigraphy in reconstruction of the development of lakes.